Antivirals for COVID-19: A critical review (2020)
No specific drugs have been approved for coronavirus disease 2019 (COVID-19) to date as the development of antivirals usually requires time. Therefore, assessment and use of currently available antiviral drugs is critical for a timely response to the current pandemic. Here, we have reviewed anti-SARS-CoV-2 potencies of available antiviral drug groups such as fusion inhibitors, protease inhibitors, neuraminidase inhibitors, and M2 ionchannel protein blockers. Although clinical trials to assess the efficacy of these antivirals are ongoing, this review highlights important information including docking and modeling analyses, in vitro studies, as well as results from clinical uses of these antivirals against COVID-19 pandemic.